EVALUATION OF CARBON PRICING IMPACTS ON THE OIL AND GAS INDUSTRY OF KAZAKHSTAN - Rakhimzhanov, Sultan; Zhalgabay, Dauren; Bokeikhanov, Dauren (Nazarbayev University, Graduate School of Public Policy, 2023)
This paper’s main research area is the extent to which carbon pricing has an impact on Kazakhstan's oil & gas industry. For this purpose, the research overviews the necessary energy policy reforms considering climate change issues and addressing the economic and social impacts of such reforms around the globe. It closely analyzes carbon pricing, particularly the emission trading systems of the world. The research identifies that Kazakhstan faces serious environmental issues and works on resolving it through environment-oriented policies and the Kazakhstan Emission Trading System (KZ ETS). The energy sector is the main emitter of greenhouse gases, and oil & gas sector is responsible for approximately 45% of energy consumption. Since the oil & gas sector is a private sector with access to international expertise in sustainability knowledge and sufficient funds to modernize equipment and introduce new technologies, it was chosen as the target for this research. Research conducts the overview of the KZ ETS system with references and comparisons to the international experience. It conducts the qualitative research in the form of interviews with the sample of specialists from the field of oil & gas, environment protection and state administration to identify the issues of KZ ETS and its potential to influence oil & gas companies.
Keywords: Type of access: Restricted; carbon pricing; oil and gas industry in Kazakhstan; greenhouse gases emission